IMPLEMENTATION OF STORY-BASED APPROACH IN TEACHING GRAMMAR FOR ELEMENTARY LEARNERS - Nishanbayeva, Nozima Zafarjon qizi (Educational Research in Universal Sciences, 2023)
In this research article, the usage of a story-based approach to teaching grammar is highlighted among elementary learners of grades 3-4. The purpose of this exploratory action research is to analyze the importance and effectiveness of a story-based approach in improving students’ skills in grammar. A group of elementary school learners was involved in the process. Before the action Phase questionnaires in Google form, informal interviews with colleagues and students were completed. Based on the findings action plan was created and experienced in the classroom. Findings, action plans, and results were explained in detail in the following paragraphs.